Heart‐type fatty‐acid‐binding protein (FABP3) is a lysophosphatidic acid‐binding protein in human coronary artery endothelial cells. Issue 1 (31st October 2014) - Tsukahara, Ryoko; Haniu, Hisao; Matsuda, Yoshikazu; Tsukahara, Tamotsu
Abstract : Fatty‐acid‐binding protein 3, muscle and heart (FABP3), also known as heart‐type FABP, is a member of the family of intracellular lipid‐binding proteins. It is a small cytoplasmic protein with a molecular mass of about 15 kDa. FABPs are known to be carrier proteins for transporting fatty acids and other lipophilic substances from the cytoplasm to the nucleus, where these lipids are released to a group of nuclear receptors such as peroxisome proliferator‐activated receptors (PPARs). In this study, using lysophosphatidic acid (LPA)‐coated agarose beads, we have identified FABP3 as an LPA carrier protein in human coronary artery endothelial cells (HCAECs). Administration of LPA to HCAECs resulted in a dose‐dependent increase in PPARγ activation. Furthermore, the LPA‐induced PPARγ activation was abolished when the FABP3 expression was reduced using small interfering RNA (siRNA). We further show that the nuclear fraction of control HCAECs contained a significant amount of exogenously added LPA, whereas FABP3 siRNA‐transfected HCAECs had a decreased level of LPA in the nucleus. Taken together, these results suggest that FABP3 governs the transcriptional activities of LPA by targeting them to cognate PPARγ in the nucleus. Abstract : We have identified FABP3 as an LPA carrier protein in human coronary artery endothelial cells (HCAECs). Administration of LPA to HCAECs resulted in a dose‐dependent increase in PPARγ activation. LPA‐induced PPARγ activation was abolished when the FABP3 expression was reduced using small interfering RNA (siRNA). FABP3 governs the transcriptional activities of LPA by targeting them to cognate PPARγ in the nucleus.